2023
DOI: 10.1021/acs.inorgchem.2c04048
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electronic Properties of Ba2MnSe3

Abstract: The structural, thermal, and electronic properties of Ba2MnSe3 were investigated. Analysis of the low-temperature heat capacity revealed a low Debye temperature and a low average speed of sound that, together with the bonding in this material, result in a low thermal conductivity over a relatively large temperature range. Density functional theory and calculated electron localization were employed to investigate the electronic structure and bonding. Absorption and photoluminescence spectroscopy measurements co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…25 It has also recently been reported that Ba 2 MnSe 3 exhibits low thermal conductivity over a broad temperature range. 26 Given the unconventional properties which emerge from this structural motif, our selected material to showcase the capabilities of this innovative synthetic methodology is Ba 2 MnS 3 , a quasi-1D chain magnet with an undetermined magnetic ground state.…”
Section: Introductionmentioning
confidence: 99%
“…25 It has also recently been reported that Ba 2 MnSe 3 exhibits low thermal conductivity over a broad temperature range. 26 Given the unconventional properties which emerge from this structural motif, our selected material to showcase the capabilities of this innovative synthetic methodology is Ba 2 MnS 3 , a quasi-1D chain magnet with an undetermined magnetic ground state.…”
Section: Introductionmentioning
confidence: 99%